IgA in human health and diseases: Potential regulator of commensal microbiota - Takeuchi, Tadashi; Ohno, Hiroshi (Frontiers in Immunology, 2022)
Gut microbiota has extensive and tremendous impacts on human physiology and pathology. The regulation of microbiota is therefore a cardinal problem for the mutualistic relationship, as both microbial overgrowth and excessive immune reactions toward them could potentially be detrimental to host homeostasis. Growing evidence suggests that IgA, the most dominant secretory immunoglobulin in the intestine, regulates the colonization of commensal microbiota, and consequently, the microbiota-mediated intestinal and extra-intestinal diseases. In this review, we discuss the interactions between IgA and gut microbiota particularly relevant to human pathophysiology. We review current knowledge about how IgA regulates gut microbiota in humans and about the molecular mechanisms behind this interaction. We further discuss the potential role of IgA in regulating human diseases by extrapolating experimental findings, suggesting that IgA can be a future therapeutic strategy that functionally modulates gut microbiota.